Surgical management for intracranial hemorrhage in neonates and infants with hemophilia - Harada, Atsuko; Fukuya, Shogo; Hattori, Yuka; Ishimori, Shingo; Toyoda, Saori; Kawamoto, Saki; Yamanaka, Takumi; Onishi, Satoshi; Wada, Yuki; Maeno, Kazushige; Okizuka, Yo (Nervous System in Children, 2023)
Hemophilia is a rare X-linked recessive bleeding disease caused by a deficiency of blood factors VIII and IX for hemophilia A and B, respectively. Intracranial hemorrhage (ICH) is the most serious event in hemophilia patients and results in high rates of mortality and disability, especially in younger children, even though it occurs only 1-4% of this population. However, approximately 20-30% of hemophilia is sporadic and cannot be diagnosed at the time of ICH onset. Herein, we present two cases of intracranial hemorrhage in children with hemophilia without family history.Case 1 involved a seven-day-old neonate with severe hemophilia A. He was born via normal vaginal delivery at 37 weeks and 5 days. His Apgar score was 9 at 1 minute and 10 at 5 minutes. He was sufficiently healthy to be discharged home on day 5, but was brought to the emergency room on day 7 for nausea and a feeding disorder. His anterior fontanelle was bulging and a CT scan revealed a right subdural hematoma with a midline shift. He underwent surgical treatment for hematoma with craniotomy. The surgery was successful; however, a postoperative blood examination revealed high APTT. We initiated factor VIII and IX concentrate and fresh frozen plasma (FFP) infusion postoperatively, until severe hemophilia A was diagnosed. At the seven-year follow-up, he could walk independently, but exhibited moderate left hemiparesis and severe developmental delay.Case 2 involved a three-month-old infant with severe hemophilia B. He was born by caesarean section at 39 weeks and 3 days and was raised without any difficulties. At the age of 3 months, he was brought to the emergency room for vomiting and lethargy. He had right moderate hemiparesis, and a CT scan revealed a left intracerebral hematoma spreading from the frontal to the temporal lobe, with ventricular perforation. We suspected hemophilia due to a prolonged APTT, and he was administered FFP before the ventricular reservoir placement. The surgery was successful, and we continued infusing FFP for 8 days until we obtained factor IX concentrate. At the 1-year and 1-month follow-up, his right hemiparesis had recovered, but exhibited mild developmental delay.When a child has ICH, spontaneous ICH caused by coagulopathies such as hemophilia should be suspected, as well as an accidental head trauma or abuse. In the event of emergency surgery when coagulation factor concentrate cannot be prepared immediately, FFP may be used for perioperative coagulation management.